The regular schooling and the formal Environmental Education: rising, principles and normative elements - Lana, Zilda Maria de Oliveira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The present essay aims to discuss the Environmental Education within regular school considering the historical path of its insertion and the main normative elements that rules it. For that, the study is divided in three sections. Firstly, before going to the Environmental Education's specifics, there's the concern of familiarizing the reader about the Brazilian formal education bringing, in the two first sections of the essay, laws and principles that guide the different levels and modalities of education. Following, in the three last sections, discussing Environmental Education, it gives attention to a brief historical background on the rising of this field of knowledge and then discussing the rules that regulate its practice in regular education. Lastly, it illustrates with some academic works a little bit of the school practice in Environmental Education realized by some different levels and modalities of teaching within the country.